Congenital Hypothyroidism: A Severely Neglected Case Report in Bangladesh (Bangladesh Medical Journal, 2014)
A 6 year old girl presented with not growing well, delayed milestone of development, feeding difficulty, constipation since birth and breathing difficulty for last 3 months. The diagnosis was congenital hypothyroidism which was confirmed by Serum FT4 & TSH. The patient was put on oral thyroxin and showed little improvement initially and discharged on request after 15 days but unfortunately she died after 1 month at her residence. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18787 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 59-61